Polylactic acid fiber and spinning process thereof
By blending the heat-resistant and ultraviolet-resistant agent PLA-TiO2-N/SiO2 with polylactic acid slices and preparing it through a specific spinning process, the problem of insufficient UV resistance and heat resistance of polylactic acid fibers is solved, and polylactic acid is realized The fiber has excellent UV resistance and heat resistance.
Patent Information
- Application Number
- CN202411799667.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-14
AI Technical Summary
Polylactic fibers have poor UV resistance and heat resistance, cannot effectively protect the skin and show instability at high temperatures.
Thermal-resistant and UV-resistant PLA-TiO2-N/SiO2 and polylactic acid slices were prepared by melt blending the heat-resistant and UV-resistant polylactic acid slices, and the heat-setting process was prepared with a heat-spinning, winding, drafting and heat-setting process. Polylactic fiber with excellent UV resistance and heat resistance.
The UV resistance and heat resistance of polylactic fibers are significantly improved, allowing them to effectively protect the skin and remain stable at high temperatures.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical fiber preparation, and in particular to a polylactic acid fiber and a spinning process thereof. Background Art
[0002] As an indispensable part of daily life, textiles are consumed in large quantities and there are challenges in recycling and reuse, and their impact on the environment cannot be ignored. Therefore, the development of new sustainable biodegradable textile materials has become an important direction for the development of global textile technology. In recent years, polylactic acid fiber, as a new fiber material, has received widespread attention and favor from the global textile industry. This fiber is derived from renewable resources, such as corn and other grains, and is made into a biodegradable chemical fiber, which solves the problem of traditional polymer materials relying on petrochemical resources. Polylactic acid fiber can be completely decomposed in water or soil without causing pollution to the environment. Therefore, it has wide application potential in many fields such as biomedicine, packaging, clothing and home textiles, and is considered to be one of the most promising bio-based degradable materials on the market.
[0003] Polylactic acid fiber has poor UV resistance because its molecular structure lacks structural units such as benzene rings that can absorb UV rays, resulting in a high UV transmittance. Textiles with high UV transmittance cannot provide necessary protection for the skin when used as summer clothing, especially white and light-colored clothing, and are harmful to human health. In addition, polylactic acid fiber also has poor heat resistance. Summary of the invention
[0004] In order to overcome the deficiencies of the prior art, the object of the present invention is to provide a polylactic acid fiber and a spinning process thereof to solve the technical problems of poor UV resistance and poor heat resistance of the polylactic acid fiber.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A spinning process of polylactic acid fiber comprises the following steps:
[0007] (1) melt-blending the heat-resistant and anti-ultraviolet agent PLA-TiO2-N / SiO2 with polylactic acid slices to obtain heat-resistant and anti-ultraviolet polylactic acid slices;
[0008] (2) The heat-resistant and UV-resistant polylactic acid chips are melt-spun, wound, drawn, and heat-set to obtain polylactic acid fibers.
[0009] Furthermore, the temperature of the melt blending in step (1) is 180-200°C.
[0010] Furthermore, the amount of the heat-resistant and anti-ultraviolet agent PLA-TiO2-N / SiO2 used in step (1) is 0.25-1wt% of the total mass of the polylactic acid slice.
[0011] Furthermore, in step (2), the temperature of melt spinning is 220-240°C; the winding speed is 400-600 m / min; the drawing temperature is 140-150°C; the drawing ratio is 4-6 times; and the heat setting temperature is 120-130°C.
[0012] Further, the preparation steps of the heat-resistant and UV-resistant agent PLA-TiO2-N / SiO2 include:
[0013] S1. Preparation of PLA-TiO2 by grafting polylactic acid with titanium dioxide:
[0014] After L-lactic acid and anatase nano-titanium dioxide are ultrasonically treated at room temperature for 0.5-1h, the pressure is reduced to 0.07MPa and heated to 150-160°C for stirring and reacting for 2-3h to obtain a reaction solution; stannous chloride catalyst is added to the reaction solution under nitrogen protection, and then the vacuum degree is increased to 0.09-0.095MPa and heated to 170-180°C for reaction for 7-8h to obtain a product, which is then cooled to room temperature and the vacuum is released; the product is washed with dichloromethane, centrifuged, washed with hydrochloric acid, washed with anhydrous ethanol, and dried to obtain PLA-TiO2;
[0015] S2, preparation of amino silicon dioxide:
[0016] The silica and KH550 solution is heated to 80-90°C and stirred for 5-6 hours, and then dried, ground, washed, vacuum filtered and dried to obtain amino silica;
[0017] S3. PLA-TiO2 grafted with amino-silica to prepare PLA-TiO2-N / SiO2:
[0018] Dissolve PLA-TiO2 in dichloromethane, heat to 90-100°C, add amino silicon dioxide, keep warm for 4-5 hours, filter, wash and dry to obtain PLA-TiO2-N / SiO2.
[0019] Furthermore, the mass ratio of L-lactic acid, anatase nano-titanium dioxide and stannous chloride catalyst in S1 is 50:1:0.25.
[0020] Further, the amount of KH550 in S2 is 3-5wt% of the mass of silica;
[0021] The mass ratio of water:methanol:KH550 in the KH550 solution is 10:70:20.
[0022] Furthermore, the mass ratio of PLA-TiO2 to amino silica is 5:1-3.
[0023] A polylactic acid fiber is prepared by the spinning process.
[0024] Beneficial effects of the present invention:
[0025] (1) The present invention prepares PLA-TiO2-N / SiO2 as a heat-resistant and anti-ultraviolet agent, so that the polylactic acid fiber obtained by spinning has excellent ultraviolet resistance and heat resistance.
[0026] (2) The present invention utilizes the ultraviolet shielding function of titanium dioxide to improve the anti-ultraviolet function of polylactic acid fiber. In the preparation process, polylactic acid is first grafted onto titanium dioxide, and KH550 is used to amino-modify silica so that silica is also grafted onto polylactic acid to prepare PLA-TiO2-N / SiO2 having both heat-resistant and anti-ultraviolet effects. The grafting of polylactic acid into the heat-resistant anti-ultraviolet agent improves its compatibility with polylactic acid fiber, thereby improving its dispersibility in polylactic acid fiber, which can better exert its heat-resistant and anti-ultraviolet effects. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] This embodiment provides a polylactic acid fiber, which is prepared by the following spinning process:
[0030] (1) melt-blending a heat-resistant and anti-ultraviolet agent PLA-TiO2-N / SiO2 with a polylactic acid slice at 200° C. to obtain a heat-resistant and anti-ultraviolet polylactic acid slice, wherein the amount of PLA-TiO2-N / SiO2 is 0.25 wt % of the total mass of the polylactic acid slice;
[0031] (2) The heat-resistant and UV-resistant polylactic acid chips were melt-spun at 240° C., wound at a speed of 600 m / min, stretched at 150° C. at a stretching ratio of 6 times, and heat-set at 130° C. to obtain polylactic acid fibers.
[0032] The preparation steps of the heat-resistant and UV-resistant agent PLA-TiO2-N / SiO2 include:
[0033] S1. Preparation of PLA-TiO2 by grafting polylactic acid with titanium dioxide:
[0034] 100g L-lactic acid and 2g anatase nano-titanium dioxide were ultrasonically treated at room temperature for 1h, then the pressure was reduced to 0.07MPa and heated to 160°C for stirring and reaction for 3h to obtain a reaction solution; 0.5g stannous chloride catalyst was added to the reaction solution under nitrogen protection, and then the vacuum degree was increased to 0.09MPa and heated to 180°C for reaction for 8h to obtain the product, which was then cooled to room temperature and released from vacuum; the product was washed with dichloromethane, centrifuged, washed with hydrochloric acid, washed with anhydrous ethanol, and dried to obtain PLA-TiO2;
[0035] S2, preparation of amino silicon dioxide:
[0036] Add water and methanol to KH550 to prepare a KH550 solution with a mass ratio of water: methanol: KH550 of 10:70:20, add silica to the solution and heat to 90°C and stir to react for 6 hours. After the reaction is completed, the product is dried, ground, washed, vacuum filtered and dried to obtain amino silica. The amount of KH550 used is 3wt% of the mass of silica;
[0037] S3. PLA-TiO2 grafted with amino-silica to prepare PLA-TiO2-N / SiO2:
[0038] PLA-TiO2 was dissolved in dichloromethane, the temperature was raised to 100°C, and amino silica was added. The reaction was kept warm for 4 hours. After filtering, washing and drying, PLA-TiO2-N / SiO2 was obtained. The mass ratio of PLA-TiO2 to amino silica was 5:1.
[0039] Example 2
[0040] Compared with Example 1, the difference between this embodiment is that the "amount of PLA-TiO2-N / SiO2 is 0.25wt% of the total mass of the polylactic acid slice" in step (1) is changed to "the amount of PLA-TiO2-N / SiO2 is 0.5wt% of the total mass of the polylactic acid slice"; the remaining raw materials and preparation process remain the same as in Example 1.
[0041] Example 3
[0042] Compared with Example 1, the difference between this embodiment and Example 1 is that the "amount of PLA-TiO2-N / SiO2 is 0.25wt% of the total mass of the polylactic acid slice" in step (1) is changed to "the amount of PLA-TiO2-N / SiO2 is 1wt% of the total mass of the polylactic acid slice"; the remaining raw materials and preparation process remain the same as in Example 1.
[0043] Example 4
[0044] The difference between this embodiment and embodiment 3 is that the "amount of KH550 is 3wt% of the mass of silicon dioxide" in step S2 is changed to "the amount of KH550 is 4wt% of the mass of silicon dioxide"; the remaining raw materials and preparation process remain the same as those in embodiment 3.
[0045] Example 5
[0046] The difference between this embodiment and embodiment 3 is that the "amount of KH550 is 3wt% of the mass of silicon dioxide" in step S2 is changed to "the amount of KH550 is 5wt% of the mass of silicon dioxide"; the other raw materials and preparation process remain the same as those in embodiment 3.
[0047] Example 6
[0048] The difference between this embodiment and embodiment 4 is that the "mass ratio of PLA-TiO2 and amino silica is 5:1" in step S3 is changed to "the mass ratio of PLA-TiO2 and amino silica is 5:2"; the remaining raw materials and preparation process remain the same as those in embodiment 4.
[0049] Example 7
[0050] Compared with Example 4, this embodiment differs in that the "mass ratio of PLA-TiO2 and amino silica is 5:1" in step S3 is changed to "the mass ratio of PLA-TiO2 and amino silica is 5:3"; the remaining raw materials and preparation process remain the same as in Example 4.
[0051] Comparative Example 1
[0052] Compared with Example 1, this comparative example differs in that the silica is not aminated, that is, SiO2 is used to replace the aminated silica to prepare PLA-TiO2-SiO2 as a heat-resistant and anti-ultraviolet agent; the remaining raw materials and preparation process remain the same as in Example 1.
[0053] Comparative Example 2
[0054] The difference between this comparative example and Example 1 is that titanium dioxide is not grafted with polylactic acid, and titanium dioxide and silicon dioxide are directly mixed as a heat-resistant and anti-ultraviolet agent; the other raw materials and preparation process remain the same as those in Example 1.
[0055] Comparative Example 3
[0056] Compared with Example 4, this comparative example differs in that the "mass ratio of PLA-TiO2 and amino-silica is 5:1" in step S3 is changed to "the mass ratio of PLA-TiO2 and amino-silica is 5:6"; the remaining raw materials and preparation process remain the same as in Example 4.
[0057] The performance of the polylactic acid fibers obtained in Examples 1 to 7 and Comparative Examples 1 to 3 was tested. According to the national standard GB / T 18830-2009 “Evaluation of UV protection performance of textiles”, the ultraviolet protection factor (UPF) and ultraviolet transmittance (UVA / T%) of the polylactic acid fibers were measured on a LabsphereUV-1000F textile ultraviolet protection factor tester; the thermal decomposition temperature of the polylactic acid fiber samples was tested using a thermogravimetric analyzer, and the thermal decomposition temperature when the residual mass percentage of the polylactic acid fiber was 50% was tested. The test conditions were: nitrogen flow rate of 20 mL / min, heating rate of 10°C / min, and heating to 800°C; the results are shown in Table 1:
[0058] Table 1
[0059] Test items UPF UVA / T% Thermal decomposition temperature / ℃ Example 1 52 4.2 397.1 Example 2 53 3.4 399.3 Example 3 56 2.2 401.4 Example 4 56 2.2 405.5 Example 5 56 2.2 402.3 Example 6 55 2.3 407.5 Example 7 54 2.5 409.6 Comparative Example 1 52 4.2 389.6 Comparative Example 2 41 7.4 387.3 Comparative Example 3 49 5.1 402.2
[0060] It can be seen from Table 1 that the UPF of the polylactic acid fibers prepared in Examples 1 to 7 all reached 50+, and the UVA transmittance was all below 5%, indicating that the polylactic acid fibers had excellent UV resistance. The thermal decomposition temperatures of the polylactic acid fibers prepared in Examples 1 to 7 were all relatively high, indicating that the polylactic acid fibers had excellent heat resistance.
[0061] Compared with Example 1, Example 2 and Example 3, as the amount of PLA-TiO2-N / SiO2 increases, the UPF of the polylactic acid fiber increases, the UVA transmittance decreases, and the thermal decomposition temperature increases, indicating that increasing the amount of PLA-TiO2-N / SiO2 is beneficial to improving the UV resistance and heat resistance of the polylactic acid fiber; the reason is that PLA-TiO2-N / SiO2 has good dispersibility in the polylactic acid fiber, which benefits from the grafting of polylactic acid on the PLA-TiO2-N / SiO2, which improves the compatibility of PLA-TiO2-N / SiO2 with the polylactic acid fiber, thereby improving the dispersibility of PLA-TiO2-N / SiO2 in the polylactic acid fiber.
[0062] Compared with Example 3, Example 4 and Example 5, the thermal decomposition temperature of Example 4 is higher, which means that the amount of KH550 should not be too low or too high when the silica is amino-modified. An appropriate amount of KH550 is beneficial to improving the heat resistance of the polylactic acid fiber. The reason is that an appropriate amount of KH550 can provide sufficient reaction sites to promote the chemical bonding between silica and KH550, thereby improving the surface activity and organophilicity of silica, which is beneficial to the subsequent grafting of polylactic acid, and improves the grafting efficiency and grafting density. However, when the amount of KH550 is too much, it may cause excessive coverage of the silica surface to form a dense silane layer, which will reduce the grafting efficiency, thereby affecting the compatibility of silica and polylactic acid fibers and reducing the heat resistance of polylactic acid fibers.
[0063] Compared with Example 4, Example 6 and Example 7, the thermal decomposition temperature of Example 7 is higher, which shows that increasing the proportion of amino silica in PLA-TiO2-N / SiO2 is beneficial to improving the heat resistance of polylactic acid fiber, and that amino silica can be successfully grafted into polylactic acid, thereby fully exerting its heat resistance effect in polylactic acid fiber.
[0064] Compared with Example 1, the thermal decomposition temperature of Comparative Example 1 is lower, indicating that the heat resistance of the polylactic acid fiber is reduced. The reason is that the silica has not been amino-modified, so it cannot be grafted with polylactic acid, has low compatibility with the polylactic acid fiber, cannot be well dispersed, and is easy to agglomerate.
[0065] Compared with Example 1, Comparative Example 2 has a lower UPF, an increased UVA transmittance, and a lower thermal decomposition temperature of the polylactic acid fiber, indicating that the UV resistance and heat resistance of the polylactic acid fiber are reduced. The reason is that titanium dioxide is not grafted with polylactic acid and is directly mixed with silicon dioxide. The compatibility of titanium dioxide, silicon dioxide and polylactic acid fibers is relatively low, and thus they cannot provide good heat resistance and UV resistance.
[0066] Compared with Example 4, Example 6 and Example 7, the UPF of the polylactic acid fiber is reduced, the UVA transmittance is increased, and the thermal decomposition temperature is reduced, indicating that excessively increasing the proportion of amino silica in PLA-TiO2-N / SiO2 is not conducive to improving the heat resistance and UV resistance of the polylactic acid fiber. The reason is that excessively increasing the proportion of amino silica will lead to excessively reducing the proportion of PLA-TiO2, which is not conducive to PLA-TiO2-N / SiO2 simultaneously exerting excellent UV resistance and heat resistance.
[0067] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0068] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A spinning process for polylactic acid fiber, characterized in that: The steps include: (1) melt-blending the heat-resistant and anti-ultraviolet agent PLA-TiO2-N / SiO2 with polylactic acid slices to obtain heat-resistant and anti-ultraviolet polylactic acid slices; (2) The heat-resistant and UV-resistant polylactic acid chips are melt-spun, wound, drawn, and heat-set to obtain polylactic acid fibers.
2. The spinning process of polylactic acid fiber according to claim 1, characterized in that: The temperature of the melt blending in step (1) is 180-200°C.
3. The spinning process of polylactic acid fiber according to claim 1, characterized in that: The amount of the heat-resistant and anti-ultraviolet agent PLA-TiO2-N / SiO2 used in step (1) is 0.25-1wt% of the total mass of the polylactic acid slice.
4. The spinning process of polylactic acid fiber according to claim 1, characterized in that: In step (2), the temperature of melt spinning is 220-240°C; the winding speed is 400-600 m / min; the drawing temperature is 140-150°C; the drawing ratio is 4-6 times; and the heat setting temperature is 120-130°C.
5. The spinning process of polylactic acid fiber according to claim 1, characterized in that: The preparation steps of the heat-resistant anti-ultraviolet agent PLA-TiO2-N / SiO2 include: S1. Preparation of PLA-TiO2 by grafting polylactic acid with titanium dioxide: After L-lactic acid and anatase nano-titanium dioxide are ultrasonically treated at room temperature for 0.5-1h, the pressure is reduced to 0.07MPa and heated to 150-160°C for stirring and reacting for 2-3h to obtain a reaction solution; stannous chloride catalyst is added to the reaction solution under nitrogen protection, and then the vacuum degree is increased to 0.09-0.095MPa and heated to 170-180°C for reaction for 7-8h to obtain a product, which is then cooled to room temperature and the vacuum is released; the product is washed with dichloromethane, centrifuged, washed with hydrochloric acid, washed with anhydrous ethanol, and dried to obtain PLA-TiO2; S2, preparation of amino silicon dioxide: The silica and KH550 solution is heated to 80-90°C and stirred for 5-6 hours, and then dried, ground, washed, vacuum filtered and dried to obtain amino silica; S3. PLA-TiO2 grafted with amino-silica to prepare PLA-TiO2-N / SiO2: Dissolve PLA-TiO2 in dichloromethane, heat to 90-100°C, add amino silicon dioxide, keep warm for 4-5 hours, filter, wash and dry to obtain PLA-TiO2-N / SiO2.
6. The spinning process of polylactic acid fiber according to claim 5, characterized in that: The mass ratio of L-lactic acid, anatase nano-titanium dioxide and stannous chloride catalyst in S1 is 50:1:0.
25.
7. The spinning process of polylactic acid fiber according to claim 5, characterized in that: The amount of KH550 in S2 is 3-5wt% of the mass of silica; The mass ratio of water:methanol:KH550 in the KH550 solution is 10:70:
20.
8. The spinning process of polylactic acid fiber according to claim 5, characterized in that: The mass ratio of PLA-TiO2 to amino silica is 5:1-3.
9. A polylactic acid fiber, characterized in that: The fiberglass fiber is prepared by the spinning process described in any one of claims 1 to 8.
Citation Information
Cited By
Antibacterial fiber and preparation process
CN121700542A
Antibacterial fiber and manufacturing process
CN121700542B